Study on the Optimization of Concrete and Reinforcement Steel Volume in the Superstructure Work of Multi-Story Buildings - Vina Levia Budiman; Erick Vanhalen (Structures, Infrastructure, Planning, Implementation, and Legislation, 2025)
The efficient use of materials in reinforced concrete (RC) superstructures is a critical challenge in modern construction, driven by both economic and environmental considerations. This study investigates the optimization of concrete and reinforcement steel volumes in the superstructure of a multi-story RC building by analyzing project-specific volumetric data. The research employs a quantitative approach, beginning with data collection from structural design documents, followed by structural analysis in accordance with SNI 2847:2013 and SNI 1727:2013, and concluding with optimization strategies based on comparative and algorithmic methods. The results indicate that slabs consume the largest portion of concrete, accounting for 58.93% of the total volume, while beams and columns account for 31.33% and 9.74%, respectively. Reinforcement steel consumption was more balanced, with beams (37.96%) and slabs (36.72%) dominating, and columns contributing 25.32%. These findings are consistent with global trends, where slabs and beams represent the most material-intensive components in RC structures. The study highlights the potential for optimization strategies such as reducing slab thickness, refining reinforcement detailing, or applying algorithm-based approaches like genetic algorithms and MINLP to achieve significant material savings without compromising safety. By integrating empirical volumetric data with computational optimization methods, this research provides both theoretical insights and practical recommendations to improve the structural efficiency, cost-effectiveness, and sustainability of multi-story RC buildings.